Oued Bouhlou: A new hope for the Moroccan pearl mussel - Sousa, Ronaldo Gomes (2018)
The freshwater pearl mussel Margaritifera marocana (Pallary, ) is an endemic species of Morocco being listed as critically endangered and it stands among the world's 100 most threatened species. An extensive survey was performed in the Sebou basin (total area of approximately 40,000km(2)), covering 26 different sites. Margaritifera marocana was found only in four sites limited to a small tributary (Oued (=River) Bouhlou).This population has a very restricted distribution (no more than 4km of river length) but appears stable with recent recruitment, since small specimens were found.Genetic analyses were performed, showing that this population has a similar diversity to that found in the River Laabid (Oum Er Rbia basin), but represents a distinct conservation unit that should be managed independently.Although this study adds a new population to the current known distribution of M. marocana, urgent conservation measures (e.g. extension of the Tazzekka National Park; better management of river flow; increase of the riparian vegetation in some stretches; establishment of national and international legislation, and engagement of local citizens) are needed given the species' restricted distribution, its rarity, and the numerous threats that impair its future survival.